GAMBARAN REGULASI EMOSI PADA ANAK DENGAN GANGGUAN EMOSI DAN PERILAKU (TUNALARAS) - Aisyah Miraharsari; Alfi Nadlifatul Hilmiyah (JURNAL JUDIKHU, 2023)
Emotional and behavioral disorders (deafness) can be said if a person experiences a disorder in managing emotions and behavior or social control. In this case, if the child wants to side by side, be involved, and mingle with his social environment, then the ability to manage emotions in interaction is needed. Managing these emotions can be called emotional regulation (emotion regulation). This emotion regulation is a strategy that is carried out by an individual both consciously and unconsciously in recognizing, avoiding, inhibiting, maintaining or managing emotional reactions and expressing these emotions automatically or under control, in order to fulfill biological affect or social adaptation to regulate appropriate behavior in achieve a goal. The focus in this study is more emphasis on how the emotional regulation of children with emotional and behavioral disorders (sensory impairment). The method used in this study is a qualitative research with three subjects consisting of one main subject and two significant others. The results of this study show that the subject has not been able to fully demonstrate his emotional regulation, which is when the subject evokes emotions, the subject tends to express his emotions and is less able to relieve the emotions that arise within him.